A terceirização nos serviços de alimentação coletiva em Salvador sob a ótica dos prestadores de serviço: um estudo de caso da empresa LemosPassos - Costa, Kelly Cristine da Silva (2005)
The process of outsourcing of the catering sector- that aims at serving high quality food, has made many entrepreneurs seek the expertise of companies that work on this segment. It s a sector that has been growing and standing out in the market due to the advantages that it provides to their clients. Besides the negotiation, the development of the relationship between the supplier and client can contribute to better the service and satisfy the client s needs with ease. The research used to analyze this dissertation has been carried out in some of the companies that LemosPassos caters for. It has based its content and theoretical reference on the norms and legislation that commands the outsourcing activity.